Management of Postpartum Mothers with After Pain at the Clinic: Tatalaksana Ibu Nifas Dengan After Pain di Klinik - Nurfiyana, Intan; Cholifah, Cholifah; Widowati, Hesti (Indonesian Journal of Innovation Studies, 2020)
Post partum is a period of 1-2 months after the delivery of the placenta until the uterus returns to normal. Post partum will issue lochea which comes out along with the birth of the placenta. Patients will experience complaints that will be felt in the postpartum, namely complaints of heartburn which helps the uterus to return to its shape normal. And these complaints will interfere with the patient's daily activities, namely irregular sleep patterns, feeling tired, feeling anxious. This discomfort was experienced by Mrs. A 21 years old, with 37 weeks of age complaining of stomach cramps or after pain, an assessment of these complaints has been made. And the results of the study, evaluation, and progress notes. Data has been collected by assessment, physical examination, diagnosis, and documentation by comparing the results of the data with the theory. And these complaints are normal complaints that are felt by every post partum mother. Contractions will cause different pains, namely mild, moderate, even severe pain